2015
DOI: 10.1016/j.rpped.2014.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Vitamina D em crianças e adolescentes com doença falciforme: uma revisão integrativa

Abstract: Objective:To review the literature about the prevalence of vitamin D deficiency and its consequences in children and adolescents with sickle-cell disease.Data sources:The literature survey was performed through the bibliographic databases MEDLINE; U.S. National Library of Medicine and National Institutes of Health (PubMed); Literatura Latino-Americana e do Caribe em Ciências da Saúde (Lilacs), and the Cochrane Library. The keywords were selected using Medical Heading Terms (MeSH): “vitamin D” OR “vitamin D def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“… 26 Many studies have reported a high frequency of VDD in the SCD population of different haplotypes as opposed to the non-SCD population, in study specific control groups. 13 16 Nevertheless, when compared to the healthy general population of the same ethnic group, the frequency was not much different in the SCD population. 14 This explanation is consistent with the finding in the present study, as SCD in the Eastern Province of Saudi Arabia is of the Arab-Indian haplotype, 20 whilst being of the same ethnicity.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“… 26 Many studies have reported a high frequency of VDD in the SCD population of different haplotypes as opposed to the non-SCD population, in study specific control groups. 13 16 Nevertheless, when compared to the healthy general population of the same ethnic group, the frequency was not much different in the SCD population. 14 This explanation is consistent with the finding in the present study, as SCD in the Eastern Province of Saudi Arabia is of the Arab-Indian haplotype, 20 whilst being of the same ethnicity.…”
Section: Discussionmentioning
confidence: 78%
“…The present study showed a high frequency of suboptimal 25(OH)D (insufficiency and deficiency) in SCD patients, reaching 82%, which is comparable to other studies where the frequency reached up to 96%. 13 16 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Com isso, os novos valores de referência laboratorial para os níveis de vitamina D 25 (OH) sugerem que acima de 20 ng/mL é o valor desejável para população saudável (até 60 anos), e entre 30 ng/mL e 60 ng/mL é o valor recomendado para grupos de risco como: idosos, gestantes, lactantes, pacientes com raquitismo/osteomalácia, osteoporose, pacientes com história de quedas e fraturas, causas secundárias de osteoporose (doenças e medicações), hiperparatiroidismo, doenças infamatórias, doenças autoimunes, doença renal crônica e síndromes de má absorção (clínicas ou pós-cirúrgicas) e acima de 100 ng/mL: risco de toxicidade e hipercalcemia (13) Como citado anteriormente, a vitamina D está presente na maioria das células e tecidos do corpo, sen-do uma das mais potentes reguladoras de crescimento celular tanto em células normais como em cancerosas. (14) Na Tabela 1 estão as principais causas da hipovitaminose D. (14) Tabela 1 -Principais causas da hipovitaminose D (14) Causas Exemplo…”
Section: Fisiologia Da Vitamina Dunclassified
“…Under low oxygen pressure, polymerization occurs, causing the normal shape of the RBCs to change to a scythe/middle moon shape, decreasing the life span of the RBCs [3]. This modification (HbS) causes molecules to organize into polymeric bundles when deoxygenated, giving the red blood cell an elongated and rigid form, called "scythe form" or "half-moon" [4].…”
Section: Introductionmentioning
confidence: 99%